Demodex as an etiological factor in chronic blepharitis - Czepita, Damian; Kuźna-Grygiel, Wanda; Kosik-Bogacka, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
Purpose: To present and account the results of newest experimental and clinical investigations on the role of Demodex folliculorum and Demodex brevis in the etiology of chronic blepharitis. Material and methods: A review of literature concerning the role of Demodex in the etiology of chronic blepharitis was done. Results: It has been established that: (1) Demodex folliculorum and Demodex brevis occur among humans worldwide. (2) With age the prevalence of eyelids demodicidosis rises. (3) In the course of chronic blepharitis infection of Demodex folliculorum and Demodex brevis is often observed. Conclusions: Demodex is an etiological factor in chronic blepharitis.